Biomedical Engineering and Medical Device Technology: Innovations in Life-Saving Solutions and Device Design - Dahi, Fatima Kazem Abis; Malallah, Russul Raheem; Malallah, Rafal Raheem; Abdalhassan, Narges Ali (American Journal of Botany and Bioengineering, 2025)
Biomedical engineering plays a crucial role in advancing medical device technology, yet challenges persist in optimizing device design for improved patient care. Despite significant progress, gaps remain in integrating biocompatible materials, enhancing device efficiency, and ensuring regulatory compliance. This study examines the latest innovations in biomedical engineering, focusing on medical device development, biomaterials, and emerging technologies. A qualitative analysis of recent advancements and clinical applications was conducted. Findings indicate that cutting-edge materials, AI integration, and nanotechnology have significantly enhanced the safety, functionality, and efficiency of medical devices. Results suggest that continuous interdisciplinary research is essential for sustainable innovation in biomedical engineering. The study highlights the need for robust regulatory frameworks, investment in research, and industry collaboration to drive future advancements in life-saving medical technologies.